2013
DOI: 10.4236/health.2013.512271
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and infant vitamin D status during lactation: Is latitude important?

Abstract: Background: The effect of latitude on maternal and infant vitamin D status during lactation ispresumed to be strongly associated with higher rates of deficiency in those living at higher latitudes, yet with lifestyle changes, this conclusion may no longer be correct. Objective: To ascertain if higher latitude adversely affects the vitamin D status of lactating women and their fully breastfeeding infants. Study Design/Methods: Fully breastfeeding women and their infants were eligible for participation in this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(37 reference statements)
4
3
0
Order By: Relevance
“…This was concordant with the study by Wagner CL et al showing moderate positive correlation (r – 0.42 – 0.65, p-value < 0.0001) between lactating mother-infant VD 3 levels. 19 It was also concordant with the study results by Husain et al who showed a moderate positive relation between VD 3 levels of mother and infant pair (Pearson coefficient = 0.516, P < 0.001). 20 This positive relation between Infant & maternal VD 3 concentrations (r s =0.41, P=0.001) was also highlighted by Salameh et al 21 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This was concordant with the study by Wagner CL et al showing moderate positive correlation (r – 0.42 – 0.65, p-value < 0.0001) between lactating mother-infant VD 3 levels. 19 It was also concordant with the study results by Husain et al who showed a moderate positive relation between VD 3 levels of mother and infant pair (Pearson coefficient = 0.516, P < 0.001). 20 This positive relation between Infant & maternal VD 3 concentrations (r s =0.41, P=0.001) was also highlighted by Salameh et al 21 …”
Section: Discussionsupporting
confidence: 92%
“…Maternal serum calcium in our study was comparable to the levels in a study by Wagner et al (8.98 ± 0.7 vs. 9.4 ± 0.4). 19 Similarly, maternal phosphorus in our study was comparable to the mothers recruited from Charleston, SC (4.19 ± 0.97 vs. 4.14 ± 0.62) but it was higher compared to mothers recruited from Rochester, NY (3.8 ± 0.60). A moderate positive correlation (r s – 0.55, p-value < 0.001) between the maternal and infant VD 3 was observed.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Baseline characteristics of the lactating mother and infant cohort have been published previously. 21 Our study was designed to test the primary hypothesis that the lactating woman requires substantially more dietary vitamin D than the amount received from maternal supplementation with 400 IU/day. 1,11 We based our maternal supplementation dosing on previous studies: for every 1000 IU per day vitamin D 3 , milk antirachitic activity would increase by ∼80 IU/L in a way that would sustain the nursing infant.…”
Section: What This Study Addsmentioning
confidence: 99%
“…1 ). We excluded 27 studies, mainly because the comparisons were among different doses of vitamin D without a placebo or control group [7 [15] , [24] , [35] , [40] , [45] , [51] , [55] , [57] , [58] , [29] , [64] , [65] , [68] . Also, four trials were not randomised [2] , [12] , [14] , [33] and three were done in pregnant women with chronic conditions [3] , [4] , [20] .…”
Section: Resultsmentioning
confidence: 99%